Effect of various acupuncture treatment protocols upon sepsis in wistar rats - Scognamillo-Szabo, MVR; Ferreira, S. H.; Cunha, F. Q. (New York Acad Sciences, 2004)
Sepsis is a syndrome characterized by infection and generalized inflammatory response that can lead to organ failure and death. In this study we standardize a model to investigate acupuncture's effects upon sepsis. The objectives were to study the use of acupuncture in the infectious process and to formulate acupuncture's treatment protocol for sepsis. The CLP (cecal ligation and puncture) model in rats was used to induce sepsis through bacterial entrance into the peritoneal cavity. An acupuncture treatment protocol that enhanced survival and reversed the neutrophil impairment migration toward the peritoneal cavity in rats with sepsis was achieved. It seems that acupuncture can be used for the treatment of experimental infectious processes. The effects of acupuncture and related mechanisms are discussed.
Keywords: acupuncture; sepsis; rats; neutrophil migration; cecal ligation and puncture